Negative hemodynamic response in the visual cortex: Evidence supporting neuronal origin via hemodynamic observation and two-photon imaging - Zhen Li; Lihua He; Limin Peng; Xuan Zhu; Ming Li; Dewen Hu (Brain Research Bulletin)
The positive hemodynamic response (PHR) during stimulation often co-occurs with a strong, sustained negative hemodynamic response (NHR). However, the characteristics and neurophysiological mechanisms of the NHR, especially in regions distal to the PHR, remain incompletely understood. Using intrinsic optical imaging (OI) and two-photon imaging, we observed that forelimb electrical stimulation evoked strong PHR signals in the forelimb region of the primary somatosensory cortex (S1FL). Meanwhile, NHR signals primarily appeared in the primary visual cortex (V1), with a delayed onset and lower amplitude relative to the PHR signals. Additionally, stimulation led to a reduction in cerebral blood flow (CBF) in the NHR region. Notably, there was an overall suppression of the calcium response in the NHR region, although a small proportion (14 %) of neurons exhibited concurrent activation. Axon tracing revealed cortico-cortical projections from S1FL to V1. These findings suggest that neuronal deactivation significantly contributes to the origin of the NHR, offering additional insights into the specific inhibitory mechanisms underlying the NHR.